IMPLEMENTASI TEKNIK SEO DALAM MENINGKATKAN TRAFFIC SERP PADA WEB STUDI KASUS (KOPERASI SYARIAH BMI) - Fithri Wulandari; Taufik Hidayat; Hanifatul Riskiya Lubis; Rifal Multiansyah (Journal of Innovation And Future Technology, 2025)
Benteng Micro Indonesia Sharia Cooperative or abbreviated as Kopsyah BMI. Kopsyah BMI is a sharia microfinance institution that is committed to improving community welfare through various sharia financial products and services. One of the services offered by Kopsyah BMI is the management of ZISWAF (Zakat, Infaq, Alms and Waqf) funds. The use of a website to promote a service available at ZISWAF is considered ineffective, because the website has not been able to reach first place in the search engine results page or SERP. In fact, it is difficult for searchengines to find it because there are so many competing websites that already exist. So it affects the number of visitors to the website. The researchmethod that will be used in this research is the SDLC (system Development Life Cycle) method. This SDLC method is a method used to develop asystem or technique which consists of stages including planning, analysis, design, implementation, testing, evaluating (maintenance) stages. This research produces and increases SERP traffic on the Ziswaf website which has been optimized using SEO technique and has been tested. Thisresearch aims to implement SEO techniques on the Ziswaf website, Benteng Mikro Indonesia Sharia Cooperative. In implementing SEO techniques, the main focus is on On Page SEO and Off Page SEO techniques.